Gallium-containing pseudo-boehmite, gallium oxide-aluminum oxide compound and preparation method of gallium-containing pseudo-boehmite

By placing the gallium-aluminum alloy solution with hot water in a protective atmosphere, a gallium-containing pseudo-thin alumina stone without impurities was generated, and a gallium-alumina composite was prepared by baking, the impurity metals, environmental pollution and insufficient catalytic performance in the preparation method of gallium-alumina catalyst in the prior art were solved, and efficient and environmentally friendly catalyst preparation was achieved.

CN119591139AActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311168354.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

The existing gallium oxide-alumina catalyst preparation methods have problems such as impurity metals, environmental pollution and insufficient catalytic performance.

Method used

By placing a gallium-aluminum alloy solution under a protective atmosphere and reacting with hot water, gallium-containing pseudo-thin alumina stone containing no impurity metals is produced, and then calcined, a gallium-alumina composite with a large specific surface area and large pore volume is prepared.

Benefits of technology

The efficient preparation of gallium oxide-alumina composite is achieved, with good catalytic properties, simple and environmentally friendly processes, and does not produce sewage discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591139A_ABST
    Figure CN119591139A_ABST
Patent Text Reader

Abstract

The invention relates to a gallium-containing pseudo-boehmite and a gallium oxide-aluminum oxide compound, and the gallium-containing pseudo-boehmite comprises the following components in percentage by weight: 0.05 to 8.5 percent of gallium, 30.0 to 45.0 percent of aluminum, and the balance of aluminum and unavoidable impurities, and is characterized in that the gallium-containing pseudo-boehmite is prepared from the following components in percentage by weight: 0.05 to 8.5 percent of gallium and 30.0 to 45.0 percent of aluminum; xRD (X-Ray Diffraction) characterizes that diffraction peaks exist when the angle 2 theta is 13.1 + / -1 degrees, 27.8 + / -1 degrees, 38.4 + / -1 degrees, 49.3 + / -1 degrees and 64.7 + / -1 degrees. The preparation method of the gallium-containing pseudo-boehmite comprises the following steps: preparing a gallium-aluminum alloy solution, reacting the gallium-aluminum alloy solution with hot water, and separating the gallium-containing pseudo-boehmite. In the gallium oxide-aluminum oxide compound, the content of gallium in terms of oxide is 0.1 wt%-12.0 wt%, the mass ratio of aluminum oxide to gallium oxide is 7-1000, the pore volume is 0.35-1.20 mL / g, the specific surface area is 180-500 m < 2 > / g, and the most probable pore diameter is 4.0-10.0 nm. The obtained gallium-containing pseudo-boehmite and gallium oxide-aluminum oxide compound hardly contains impurity elements, the pore volume and the specific surface area are large, no sewage is discharged in the preparation process, and the operation is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carrier materials and preparation thereof, and in particular relates to a gallium-containing pseudo-boehmite and a gallium oxide-aluminum oxide composite and respective preparation methods thereof. Background Art

[0002] Alumina has a certain pore structure and specific surface area, and can be used as a carrier of supported catalysts, ceramics and other materials. The specific surface area, pore volume, purity, etc. of alumina have a great influence on the performance of the product. Alumina is mainly prepared by mixing aluminum precursors through precipitation, filtration, washing, drying, roasting and other steps. The physical and chemical properties of alumina vary greatly due to different preparation methods. Traditional methods for producing alumina include alcohol aluminum method, carbonization method, aluminate neutralization method, etc. Except for the alcohol aluminum method, other methods will mostly produce salt-containing wastewater, which can pollute the environment if not treated, and alumina often contains a certain amount of impurities, which affects the quality of alumina.

[0003] Gallium metal, as a catalytically active metal, is widely used in the field of catalysis, especially in petrochemical catalysis. Gallium zeolite catalysts prepared with gallium nitrate as raw material and alumina-supported catalysts are used for the selective catalytic reduction of NO produced under lean combustion conditions by hydrocarbons. X It has good activity. Alumina is modified by gallium oxide, which can provide a large number of redox sites and acidic sites for the catalyst, and increase the adsorption and desorption capacity of the catalyst surface for the reaction gas, which can greatly increase the conversion rate and selectivity of the catalytic reaction at a lower gallium content. However, the gallium oxide-alumina currently obtained mainly includes impregnation method and atomic deposition method. The gallium oxide-alumina prepared by the two methods have problems such as insufficient interaction force and impurities, which affect the performance of gallium oxide-alumina. On the other hand, the pore size and specific surface area of ​​the obtained gallium oxide-alumina are small. When prepared by the impregnation method, the gallium source is generally gallium nitrate, gallium chloride, gallium sulfate or an organic gallium source, which will produce nitrogen oxide emissions during the subsequent roasting process, and the preparation process is complicated. When the atomic deposition method is used, an acidic and / or alkaline environment is required during the preparation process, which will produce environmentally unfriendly wastewater. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a gallium-containing pseudo-boehmite without other metal impurities and a gallium oxide-aluminum oxide composite with a large specific surface area and a large pore volume, and also provides a preparation method of the gallium oxide-aluminum oxide composite. Specifically, the present invention mainly includes the following contents.

[0005] First, the present invention provides a gallium-containing pseudo-boehmite, wherein, in terms of element, the mass content of gallium is 0.05wt%-8.5wt%, preferably 0.1wt%-8.0wt%, and more preferably 0.15wt%-7.0wt%; the mass content of aluminum is 30.0wt%-45.0wt%, preferably 32.0wt%-43.0wt%, and more preferably 34.0wt%-41.0wt%; and XRD characterization shows that the 2θ angle has diffraction peaks at 13.1±1°, 27.8±1°, 38.4±1°, 49.3±1°, and 64.7±1°. Preferably, the gallium-containing pseudo-boehmite substantially does not contain other metal elements except gallium and aluminum. Wherein, the substantially free of other elements except gallium, aluminum, hydrogen and oxygen means that the mass content of other elements is less than 0.01wt%.

[0006] Secondly, the present invention provides a gallium oxide-aluminum oxide composite, wherein the gallium content calculated as oxide is 0.1wt%-12.0wt%, the mass ratio of aluminum oxide to gallium oxide is 7-1000, the pore volume is 0.35-1.20mL / g, and the specific surface area is 180-500m 2 / g, and the most probable pore diameter is 4.0-10.0nm. Preferably, in the gallium oxide-aluminum oxide composite provided by the present invention, the gallium content calculated as oxide is 0.5wt%-10.0wt%, more preferably 1.0wt%-8.0wt%; the pore volume is 0.45-1.00mL / g, more preferably 0.50-0.90mL / g; the specific surface area is 200-450m 2 / g, more preferably 200-400m 2 / g; the most probable pore diameter is 4.5-9.0nm, more preferably 5.0-8.5nm.

[0007] Finally, the present invention also provides a method for preparing the gallium oxide-aluminum oxide composite, comprising calcining the gallium-containing pseudo-boehmite provided by the present invention, wherein the calcination conditions include: a calcination temperature of 500-800°C and a calcination time of 0.5-12 hours; preferably, the calcination temperature is 550-750°C and the calcination time is 1-10 hours.

[0008] Compared with the prior art, the gallium-containing pseudo-boehmite and gallium oxide-alumina composite provided by the present invention basically do not contain impure metal elements, and the gallium oxide-alumina composite has a large specific surface area and a large pore volume. The preparation method of the gallium-containing pseudo-boehmite and gallium oxide-alumina composite described in the present invention has a simple process and few steps. In addition, the metal gallium can be recycled repeatedly, and the impurity metal content of the product is low. The present invention is green and environmentally friendly, does not generate sewage discharge, and no nitrogen oxides are emitted during the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1This is the XRD pattern of the gallium-containing pseudo-boehmite prepared in Example 1. DETAILED DESCRIPTION

[0010] First of all, it should be noted that the endpoints and any values ​​of the ranges disclosed in this specification are not limited to the exact ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0011] In order to obtain the gallium-containing pseudo-boehmite provided by the present invention, the present invention provides a preferred preparation method, comprising the following steps: (1) preparing a gallium-aluminum alloy solution under a protective atmosphere; (2) adding the gallium-aluminum alloy solution to hot water, and standing the solution after the reaction is completed, wherein the upper layer of the reaction system is a suspension of the gallium-containing pseudo-boehmite; the temperature of the hot water is not less than 60°C; (3) separating the upper suspension in step (2), and drying the obtained solid to obtain the gallium-containing pseudo-boehmite; the drying conditions include: a drying temperature of 100-150°C and a drying time of 4-12 hours.

[0012] In the above preparation method, the preparation of the gallium-aluminum alloy solution in step (1) is a conventional operation. Preferably, the purity of the metal aluminum used to prepare the gallium-aluminum alloy is above 99%, more preferably above 99.9%, and the purity of gallium is above 99.9%, more preferably above 99.99%. Of course, the gallium-aluminum alloy obtained by other means or a commercial gallium-aluminum alloy can also be directly used. Preferably, the mass content of impurities in the gallium-aluminum alloy is less than 1000 ppm, more preferably less than 100 ppm, and further preferably less than 10 ppm. In order to prevent the gallium-aluminum alloy from being oxidized in the air, the gallium-aluminum alloy is preferably placed under a protective atmosphere, which is a gas atmosphere that does not react with gallium and aluminum, and the gas is selected from one or more of nitrogen or an inert gas.

[0013] The present invention has no specific requirements for the mass ratio of metallic gallium to metallic aluminum in the gallium-aluminum alloy, and can be adjusted accordingly according to the requirements for the gallium content and aluminum content in the target product. Preferably, in the gallium-aluminum alloy solution, metallic gallium accounts for 70% to 99% by mass, and metallic aluminum accounts for 1% to 30% by mass.

[0014] In order to successfully realize the reaction in step (2), the gallium-aluminum alloy needs to be made into a flowing solution state. The temperature of the gallium-aluminum alloy can be above 30°C, but should not be too high. It should be controlled below 70°C, or 35-65°C. Usually, heating method can be used to make the gallium-aluminum alloy reach the target temperature.

[0015] According to the present invention, when performing the reaction in step (2), there is no specific requirement for the ratio of the gallium aluminum alloy to the hot water, which can be adjusted according to actual needs. Generally, the mass ratio of the hot water to the gallium aluminum alloy is 3:1 to 20:1, preferably 4:1 to 10:1. In the preparation method provided by the present invention, the temperature of the hot water can be preferably 65°C-100°C.

[0016] In order to make the alloy react with hot water more quickly and completely, the gallium-aluminum alloy can be contacted with the hot water by adding it dropwise. Preferably, the adding is completed within 0.2-10 minutes. More preferably, the gallium-aluminum alloy is added to the hot water under stirring at a speed of 100-1000rpm.

[0017] According to the present invention, the method for separating the upper suspension in step (2) in step (3) of the preparation method can adopt the commonly used operation methods in the art, as long as the gallium oxide-aluminum oxide can be separated from the suspension, such as centrifugation, filtration or suction filtration; more preferably, after separation, deionized water is preferably used for one or more washings.

[0018] The purpose of drying in the preparation method of the present invention is to remove the physical water mixed in the gallium-containing pseudo-boehmite, and the chemical composition and structure of the product will not be destroyed thereby.

[0019] The present invention also provides a gallium oxide-aluminum oxide composite, preferably, the gallium oxide-aluminum oxide composite substantially does not contain other elements except aluminum, gallium, hydrogen and oxygen. As mentioned above, substantially does not contain other elements except aluminum, gallium, hydrogen and oxygen means that the mass content of other elements is less than 1000ppm, more preferably less than 100ppm, and further preferably less than 10ppm.

[0020] The present invention further provides a method for preparing the above-mentioned gallium oxide-aluminum oxide composite, comprising calcining the gallium-containing pseudo-boehmite according to any one of claims 1 to 9, wherein the calcination conditions include: a calcination temperature of 500-800°C and a calcination time of 0.5-12 hours; preferably, the calcination temperature is 550-750°C and the calcination time is 1-10 hours.

[0021] The present invention will be further explained below through specific preferred embodiments, but it should be noted that the present invention is not limited by the conditions of the embodiments.

[0022] The N2 adsorption and desorption characterization method is as follows: N2 adsorption and desorption characterization is performed on a Micromeritics ASAP 2420 adsorption instrument to obtain the specific surface area, pore volume and most probable pore diameter. Before the test, about 0.3 g of sample powder is taken and pretreated at 350°C and vacuum for 10 hours.

[0023] The specific method for determining the main element composition and impurities of the sample is as follows: after the sample powder is pressed into tablets, the characteristic spectral lines of each element are determined using the Rigaku Corporation 3271 X-ray fluorescence spectrometer, and the content of each element is semi-quantitatively analyzed using the external standard method to obtain the composition of Al2O3, Ga2O3, etc. in the sample.

[0024] The XRD characterization method is: take a certain amount of sample powder and press it into a sheet, and use Philips XPERT series X-ray powder diffractometer to determine the crystal form of the sample. The test conditions are: CuKα ray (Kα = 0.154nm), working current 30mA, working voltage 40kV, Ni filter, scanning range 2θ = 5° ~ 70°.

[0025] Example 1

[0026] Take 1.2 parts by mass of metal aluminum blocks (purity 99.9%) and 10.0 parts by mass of metal gallium (purity 99.99%) and place them in a container. Heat the container to 35°C in a N2 atmosphere and stir thoroughly to completely dissolve the aluminum into the gallium to obtain a gallium-aluminum alloy mixed solution. Subsequently, add the mixed solution dropwise into a reactor containing 50 parts by mass of water at 100°C and stir. The addition is completed in 2 minutes. After the reaction is completed, the liquid gallium at the bottom of the reaction system is separated, and the upper suspension is filtered, washed, and dried at 120°C for 6 hours to obtain product A1; A1 is calcined at 600°C for 3 hours to obtain B1. The XRD pattern of A1 is shown in Figure 1 The main peaks are the characteristic peaks of pseudo-boehmite, and the elemental composition (measured by X-ray fluorescence spectrometer, calcined at 600°C for 3 hours before measurement, the same below) is shown in Table 1. The composition of B1 is shown in Table 2, and the pore structure properties are shown in Table 3. The above results show that A1 is gallium-containing pseudo-boehmite, and B1 is a gallium oxide-aluminum oxide composite.

[0027] Comparative Example 1

[0028] Compared with Example 1, the only difference is that the water that reacts with the gallium-aluminum alloy solution is room temperature water, and the temperature is 20°C. The details are as follows: Take 1.2 parts by mass of metal aluminum blocks (purity 99.9%) and 10.0 parts by mass of metal gallium (purity 99.99%) and place them in a container, heat the container to 38°C in a N2 atmosphere, and stir it thoroughly to completely dissolve the aluminum into the gallium. Subsequently, the mixed solution is added dropwise into a reactor containing 50 parts by mass of 20°C water and stirred. The addition is completed in 2 minutes. After the reaction is completed, the liquid gallium at the bottom of the reaction system is separated, and the upper suspension is filtered, washed, and dried at 120°C for 6 hours to obtain the product DA1; DA1 is calcined at 600°C for 3 hours to obtain DB1. The XRD pattern of DA1 is similar to Figure 1The peak positions are consistent, mainly the characteristic peaks of pseudo-boehmite. The composition of DB1 is shown in Table 2, and the pore structure properties are shown in Table 3. The above results show that DA1 is a gallium-containing pseudo-boehmite and DB1 is a gallium oxide-alumina composite, but the gallium content is much lower than that of the gallium-containing pseudo-boehmite and gallium oxide-alumina composite described in the present invention.

[0029] Comparative Example 2

[0030] 10.0 parts by mass of metallic gallium (purity 99.99%) was placed in a container, and the container was heated to 38°C in a N2 atmosphere to obtain liquid gallium. Subsequently, the liquid gallium was added dropwise to 50 parts by mass of water at 100°C and stirred. The addition was completed in about half a minute, and then the heating was stopped and the liquid gallium was allowed to stand. The liquid gallium sank to the bottom of the reactor, and the upper part of the reaction system was a supernatant without suspended matter, indicating that pure elemental gallium was almost difficult to react with hot water.

[0031] Comparative Example 3

[0032] Take 1.0 parts by mass of commercial pseudo-boehmite SB powder (Sasol), prepare 0.32 mol / L gallium sulfate solution, use pore saturation impregnation method to impregnate the powder for 2 hours, dry at 120°C for 4 hours, and obtain product DA3; DA3 is calcined at 600°C for 3 hours to obtain DB3. The composition of DB3 is shown in Table 2, and the pore structure properties are shown in Table 3. The results show that DB3 contains impurities such as SO3, and the pore volume is lower than that of the gallium oxide-aluminum oxide composite described in the present invention.

[0033] Comparative Example 4

[0034] 1.0 mass part of commercially available aluminum oxide (purity 99.99%) was taken, trimethylgallium was used as gallium precursor source, O3 was used as reaction gas, and gallium oxide was deposited on the surface of aluminum oxide by atomic deposition method to prepare DB4. The composition of DB4 is shown in Table 2, and the pore structure properties are shown in Table 3. The results show that DB4 contains impurities such as C, and the gallium oxide content is low.

[0035] Example 2

[0036] 1.0 parts by mass of aluminum powder (purity 99.99%, 20 μm) and 4.0 parts by mass of gallium (purity 99.99%) were placed in a container, and the container was heated to 50°C in a N2 atmosphere, and stirred thoroughly to completely dissolve aluminum into gallium to obtain a gallium-aluminum alloy mixed solution. Subsequently, the mixed solution was added dropwise to a reactor containing 50 parts by mass of water at 75°C, and stirred for 1 minute. After the reaction was completed, the liquid gallium at the bottom of the reaction system was separated, and the upper suspension was filtered, washed, and dried at 120°C for 6 hours to obtain product A2, which was characterized by XRD and mainly had characteristic peaks of pseudo-boehmite; A2 was calcined at 550°C for 3 hours to obtain B2. The aluminum-gallium element composition of A2 is shown in Table 1, the composition of B2 is shown in Table 2, and the pore structure properties are shown in Table 3. The above results show that A2 is gallium-containing pseudo-boehmite, and B2 is a gallium oxide-aluminum oxide composite.

[0037] Example 3

[0038] 1.0 parts by mass of aluminum powder (purity 99.9%, 100 μm) and 15.0 parts by mass of gallium (purity 99.99%) were placed in a container, and the container was heated to 55°C in a N2 atmosphere, and stirred thoroughly to completely dissolve aluminum into gallium to obtain a gallium-aluminum alloy mixed solution. Subsequently, the mixed solution was added dropwise to a reactor containing 100 parts by mass of water at 95°C, and stirred for 5 minutes. After the reaction was completed, the liquid gallium at the bottom of the reaction system was separated, and the upper suspension was filtered, washed, and dried at 120°C for 6 hours to obtain product A3, which was characterized by XRD and mainly showed the characteristic peaks of pseudo-boehmite; A3 was calcined at 700°C for 3 hours to obtain B3. The aluminum-gallium element composition of A3 is shown in Table 1, the composition of B3 is shown in Table 2, and the pore structure properties are shown in Table 3. The above results show that A3 is gallium-containing pseudo-boehmite, and B3 is a gallium oxide-aluminum oxide composite.

[0039] Example 4

[0040] Take 1.0 parts by mass of aluminum foil (purity 99.5%, 0.13 mm thick) and 12.0 parts by mass of gallium (purity 99.99%) and place them in a container. Heat the container to 40°C in a N2 atmosphere and stir thoroughly to completely dissolve aluminum into gallium to obtain a gallium-aluminum alloy mixed solution. Subsequently, the mixed solution is added dropwise to a reactor containing 150 parts by mass of 80°C water and stirred for 5 minutes. After the reaction is completed, the liquid gallium at the bottom of the reaction system is separated, and the upper suspension is filtered, washed, and dried at 120°C for 6 hours to obtain product A4, which is characterized by XRD and mainly has characteristic peaks of pseudo-boehmite; A4 is calcined at 600°C for 4 hours to obtain B4. The aluminum-gallium element composition of A4 is shown in Table 1, the composition of B4 is shown in Table 2, and the pore structure properties are shown in Table 3. The above results show that A4 is gallium-containing pseudo-boehmite and B4 is a gallium oxide-aluminum oxide composite.

[0041] Table 1 Aluminum-gallium element composition of gallium-containing pseudo-boehmite

[0042] Mass content of gallium element (wt%) Aluminum content (wt%) Example 1-A1 3.6 35.4 Example 2-A2 1.1 39.2 Example 3-A3 2.9 34.9 Example 4-A4 2.4 39.2

[0043] Table 2 Characterization data of gallium oxide-aluminum oxide composite

[0044]

[0045] Table 3 Structural properties of gallium oxide-aluminum oxide composites

[0046] Pore ​​volume (mL / g) <![CDATA[Specific surface area (m 2 / g)]]> Pore ​​diameter(nm) Example 1-B1 0.56 255 6.42 Comparative Example 1-DB1 0.84 368 9.41 Comparative Example 2-DB2 -- -- -- Comparative Example 3-DB3 0.32 200 6.50 Comparative Example 4-DB4 0.66 288 7.21 Example 2-B2 0.47 216 5.29 Example 3-B3 0.82 350 8.33 Example 4-B4 0.62 298 7.82

Claims

1. A gallium-containing pseudo-boehmite, wherein: Calculated as an element, the mass content of gallium is 0.05wt%-8.5wt%, and the mass content of aluminum is 30.0wt%-45.0wt%; XRD characterization shows that the 2θ angles have diffraction peaks at 13.1±1°, 27.8±1°, 38.4±1°, 49.3±1°, and 64.7±1°.

2. The gallium-containing pseudo-boehmite according to claim 1, wherein: The gallium-containing pseudo-boehmite substantially does not contain any other elements except gallium, aluminum, hydrogen and oxygen.

3. The gallium-containing pseudo-boehmite according to claim 1, wherein: The method for preparing gallium-containing pseudo-boehmite comprises the following steps: (1) preparing a gallium-aluminum alloy solution under a protective atmosphere; (2) adding the gallium-aluminum alloy solution into hot water, and allowing the solution to stand after the reaction is completed, so that the upper layer of the reaction system is a suspension containing gallium-containing pseudo-boehmite; the temperature of the hot water is not less than 60° C.; (3) Separating the upper suspension in step (2) and drying the obtained solid to obtain gallium-containing pseudo-boehmite; the drying conditions include: drying temperature of 100-150° C. and drying time of 4-12 hours.

4. The gallium-containing pseudo-boehmite according to claim 3, wherein the protective atmosphere is a gas atmosphere that does not react with gallium and aluminum, and the gas is selected from one or more of nitrogen or inert gases.

5. The gallium-containing pseudo-boehmite according to claim 3, wherein in the gallium-aluminum alloy solution, metal gallium accounts for 70% to 99% by mass, and metal aluminum accounts for 1% to 30% by mass.

6. The gallium-containing pseudo-boehmite according to claim 3, wherein the mass ratio of the hot water to the gallium-aluminum alloy in step (2) is 3:1 to 20:1, preferably 4:1 to 10:

1.

7. The gallium-containing pseudo-boehmite according to claim 3, wherein the temperature of the hot water in step (2) is 65°C-100°C.

8. The gallium-containing pseudo-boehmite according to claim 3, wherein: In step (1), the gallium-aluminum alloy is added to the hot water dropwise, and the addition is completed within 0.2-10 minutes.

9. The gallium-containing pseudo-boehmite according to claim 3, wherein: The gallium-aluminum alloy is added into hot water under stirring conditions, and the stirring speed is 100-1000 rpm.

10. The gallium-containing pseudo-boehmite according to claim 3, wherein the method for separating the upper suspension in step (2) in step (3) is centrifugation, filtration or suction filtration, and after separation, it is preferably washed once or multiple times with deionized water.

11. A gallium oxide-aluminum oxide composite, wherein the gallium content calculated as oxide is 0.1wt%-12.0wt%, the mass ratio of aluminum oxide to gallium oxide is 7-1000, the pore volume is 0.35-1.20mL / g, and the specific surface area is 180-500m 2 / g, and the most probable pore size is 4.0-10.0nm.

12. The gallium oxide-aluminum oxide composite according to claim 11, wherein the gallium content calculated as oxide is 0.5wt%-10.0wt%, preferably 1.0wt%-8.0wt%; the mass ratio of aluminum oxide to gallium oxide is 9-200, preferably 11.5-99; the pore volume is 0.45-1.00mL / g, preferably 0.50-0.90mL / g; the specific surface area is 200-450m 2 / g, preferably 200-400m 2 / g; the most probable pore diameter is 4.5-9.0nm, preferably 5.0-8.5nm.

13. The gallium oxide-aluminum oxide composite according to claim 11, wherein The gallium oxide-aluminum oxide composite substantially does not contain elements other than aluminum, gallium, hydrogen and oxygen.

14. The method for preparing the gallium oxide-aluminum oxide composite according to claim 11, comprising calcining the gallium-containing pseudo-boehmite according to any one of claims 1 to 9, wherein the calcination conditions include: The calcination temperature is 500-800°C and the calcination time is 0.5-12 hours; Preferably, the calcination temperature is 550-750° C., and the calcination time is 1-10 hours.

Citation Information

Patent Citations

  • Iron-gallium-based propane dehydrogenation catalyst and preparation method thereof

    CN109939688A

  • Catalyst for preparing methyl isobutyl alcohol, preparation method and applications thereof

    CN110871076A

  • Method for producing hydrogen and coproducing pseudo-boehmite and / or aluminum oxide through aluminum-water reaction

    CN111807322A

  • Production method of high-purity pseudo-boehmite, and produced high-purity pseudo-boehmite

    CN111807396A

  • Preparation method of high-purity macroporous pseudo-boehmite and prepared pseudo-boehmite

    CN114314620A